Digging into the receptive and productive knowledge of phrasal verbs among Arab EFL learners: Evidence of the effect of frequency of occurrence - Albaqami, Rashidah (Linguistics and Culture Review, 2021)
Foreign language learners often encounter challenges in understanding and using English phrasal verbs (PVs) due to its idiomaticity and complexity. A phrasal verb typically comprises a verb and a preposition, e.g., pick up, look after, and result in. The study attempts to determine the extent to which frequency of occurrence facilitates or hinders mastering the target forms among English Foreign Language (EFL) learners. This study attempts to examine frequency of occurrence as a factor that might account for EFL learners’ receptive and productive knowledge of PVs. English belongs to the Germanic language family and hence it shares some common linguistic features with other members of the language family, e.g., German has detachable prefix verbs (e.g., warten auf) in a way resembling the English phrasal verb (e.g., wait for). On the other hand, other language families such as Semitic languages (e.g., Arabic), rely heavily on single word-verbs (SVs) (e.g., y?nt??r ‘wait’ in Arabic). For this purpose, a total of 37 high school female students in Jeddah (Saudi Arabia) took part in the current study.